Common mental disorders and intimate partner violence in pregnancy - Ana Bernarda Ludermir; Sandra Valongueiro; Thália Velho Barreto de Araújo (Universidade de São Paulo, 2014)
OBJECTIVE : To investigate the association between common mental disorders and intimate partner violence during pregnancy. METHODS : A cross sectional study was carried out with 1,120 pregnant women aged 18-49 years old, who were registered in the Family Health Program in the city of Recife, Northeastern Brazil, between 2005 and 2006. Common mental disorders were assessed using the Self-Reporting Questionnaire (SRQ-20). Intimate partner violence was defined as psychologically, physically and sexually abusive acts committed against women by their partners. Crude and adjusted odds ratios were estimated for the association studied utilizing logistic regression analysis. RESULTS : The most common form of partner violence was psychological. The prevalence of common mental disorders was 71.0% among women who reported all form of violence in pregnancy and 33.8% among those who did not report intimate partner violence. Common mental disorders were associated with psychological violence (OR 2.49, 95%CI 1.8;3.5), even without physical or sexual violence. When psychological violence was combined with physical or sexual violence, the risk of common mental disorders was even higher (OR 3.45; 95%CI 2.3;5.2). CONCLUSIONS : Being assaulted by someone with whom you are emotionally involved can trigger feelings of helplessness, low self-esteem and depression. The pregnancy probably increased women`s vulnerability to common mental disorders